ANALYSIS OF THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND BEHAVIOR CONTROL ON ENTREPRENEURIAL ATTITUDES AND ENTREPRENEURIAL INTENTION AMONG STUDENTS OF PELITA HARAPAN UNIVERSITY - Jayanagara, Oscar; Adijaya, Albert (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
This study is aimed at testing the variables of entrepreneurial attitude and behavioural control on entrepreneurial education and entrepreneurial intention among students of Pelita Harapan University. The subjects of this study consisted of 220 respondents who are students from various departments at Pelita Harapan University. The data collection method used in this study is quantitative, with sample selection using purposive sampling technique. Data analysis was conducted using Partial Least Square-Structural Equation Modelling (PLS-SEM) with the Smart-PLS version 4.0.9.6 application. The results show that Behavioural Control and Entrepreneurial Attitude have a positive influence on Entrepreneurial Education. Additionally, Behavioural Control and Entrepreneurial Education have a positive influence on Entrepreneurial Intention. However, Entrepreneurial Attitude has a negative impact on Entrepreneurial Intention.